Reunification and West German-Soviet Relations - Feld, Werner. author. aut Link
204 p. 1 illus.
Keywords: The intellectual debts which I have incurred in the preparation of this study are many. Foremost, I wish to express my warm appreciation and gratitude to Professor Henry L. Mason for his sound advice, gentle encouragement, and continuous guidance. In addition, I would like to extend my sincere thanks to Professors David R. Deener, Warren RobertsJr. and John L. Snell for their critical comments and helpful suggestions which led to frequent and fruitful reconsideration of the substance and form of the inquiry. I am also very grateful to Professor J. W. Smurr who made many constructive suggestions with regard to the content and style of the manuscript. A special debt is owed to Mr. Jon Reinhardt who read the manu script in its entirety and suggested a number of stylistic improvements. Richard Paulig, former Consul-General of the Federal Republic of Ger in New Orleans, La., was most helpful by assisting in the col many, lection of certain source materials, and the staff members of the Bundestag library in Bonn, Germany, under the direction of Bibliotheksoberrat Dr. Heinz Matthes aided the research for this study with outstanding efficiency. Finally, my most heartfelt expressions of gratitude are re served for my wife, Betty, whose encouragement and sympathetic understanding have helped me through this work.